Econometric Analysis of Dutch Disease Implication of China-Africa Trade (Quarterly Journal of Econometrics Research, 2021)
This study revisits the analysis of the Dutch disease implication of China-Africa trade for Africa’s non-mineral resources sectors; specifically, manufacturing and agricultural sectors, while focusing on the trade relationship between China and 27 African countries for the period of 19years, 2001 to 2019. This prompted an econometric analysis with the use of two-step dynamic (difference and system) panel Generalized Method of Moment (GMM) models, which was also complemented with dynamic least squares panel econometric regression. The preliminary analysis revealed that Ethiopia is the largest African trading partner with China, with an average of about 21percent China-Ethiopia trade ratio, while Botswana has the least trade relation with China, with 1.5percent Botswana-China trade ratio. The result of our econometric analyses suggests that higher China-Africa trade has the potential to reduce Africa’s manufacturing value-added. In other words, China-Africa trade is not causing Dutch disease in Africa but has the potential to cause Dutch disease in the future. Furthermore, the result suggests that higher China-Africa trade has the potential to increase Africa’s agricultural sector productivity. This implies that China-Africa trade has no tendency of causing Dutch disease in the agricultural sector. Our results are robust to different data structures for the dynamic GMM model.